What Makes a Trip Unforgettable? Investigating the Role of Memorable Tourism Experiences on Visitor Loyalty in Padang - Afifah; Komala Dewi, Ranti; Gustiawan, Willson (Global Review of Tourism and Social Sciences, 2025)
Tourists’ intentions to revisit and recommend a destination are pivotal for ensuring long-term sustainability within the tourism industry. This study investigates the influence of Memorable Tourism Experiences (MTE) on tourists’ behavioural intentions in Padang City, Indonesia. Employing purposive sampling, data were gathered from 213 domestic and international tourists and analysed using Structural Equation Modelling (SEM). Eight dimensions of MTE are examined: hedonism, novelty, local culture, refreshment, meaningfulness, involvement, knowledge, and adverse feelings. The findings indicate that hedonism exerts a significant positive effect on tourists’ intentions to revisit and recommend the destination. While local culture, refreshment, involvement, knowledge, and adverse feelings demonstrated positive but statistically insignificant effects, novelty and meaningfulness were found to have negative impacts on behavioural intentions. These results suggest that pleasurable experiences are central to fostering destination loyalty, whereas experiences perceived as novel or meaningful may not necessarily translate into revisitation or recommendation. The study offers practical insights for destination managers, emphasising the enhancement of enjoyable and emotionally engaging experiences. Although statistically insignificant, dimensions such as local culture, involvement, and refreshment remain valuable for shaping positive tourist perceptions and should be integrated into experience design strategies.